Organoleptic Test of Salam Leaves (Syzygium polyanthum) as an Herbal Drink with the Addition of Moringa Leaves (Moringa oleifera L.) - Kirana Pebriana; M. Idris; Rahmadina (JURNAL BIOS LOGOS, 2024)
Tea is a fresh drink made from processed tea leaves. Bay leaves and Moringa leaves are used as the main ingredients in making this tea. Syzygium polyanthum and Moringa oleifera L. plants contain the same compounds, namely flavonoids and have anti-inflammatory properties. The purpose of this study was to measure antioxidant and flavonoid levels in the making of bay leaf tea with the addition of Moringa leaves, as well as conduct organoleptic tests in Kampung Dalam Village. This research method is experimental with quantitative data analysis, using four formulations in antioxidant and flavonoid tests, namely 80%: 20%, 70%: 30%, 60%: 40%, and 50%: 50%, as well as survey method with quantitative data analysis for organoleptic properties test. The results showed that the highest antioxidant and flavonoid levels were found in the 80:20% formulation, which were 13.22 ppm and 42.7500 mQE/g. The organoleptic assessment results showed that the 50%:50% formulation had the highest level of liking at 75% with a neutral description. In addition, the 70%:30% formulation has the highest aroma level of 77.5% with a scented description, the 50%:50% formulation has the highest taste level of 70% with a tasteless description, and the 50%:50% formulation has the highest color level of 67.5% with a yellowish green description. The conclusion is that the addition of moringa leaves as an herbal drink to bay leaves has a significant effect on liking, aroma, taste and color